Crosstalk between Substrates and Rho-Associated Kinase Inhibitors in Cryopreservation of Tissue-Engineered Constructs. (19th October 2017) - Bit, Arindam; Kumar, Awanish; Singh, Abhishek Kumar; Rizvanov, Albert A.; Kiassov, Andrey P.; Patra, Pradeep Kumar; Kumar, Munish; Bissoyi, Akalabya
Abstract : It is documented that human mesenchymal stem cells (hMSCs) can be differentiated into various types of cells to present a tool for tissue engineering and regenerative medicine. Thus, the preservation of stem cells is a crucial factor for their effective long-term storage that further facilitates their continuous supply and transportation for application in regenerative medicine. Cryopreservation is the most important, practicable, and the only established mechanism for long-term preservation of cells, tissues, and organs, and engineered tissues; thus, it is the key step for the improvement of tissue engineering. A significant portion of MSCs loses cellular viability while freeze-thawing, which represents an important technical limitation to achieving sufficient viable cell numbers for maximum efficacy. Several natural and synthetic materials are extensively used as substrates for tissue engineering constructs and cryopreservation because they promote cell attachment and proliferation. Rho-associated kinase (ROCK) inhibitors can improve the physiological function and postthaw viability of cryopreserved MSCs. This review proposes a crosstalk between substrate topology and interaction of cells with ROCK inhibitors. It is shown that incorporation of ionic nanoparticles in the presence of an external electrical field improves the generation of ROCK inhibitors to safeguard cellular viability for the enhanced cryopreservation of engineered tissues.